PENGARUH BUDAYA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI MTS NURUL HIKMAH CINTAMANIS BARU - Nur Hasan (UNISAN JURNAL, 2023)
The main objectives of this research are 1) To find out the influence of work culture on teacher performance at SMK Ma’arif Sindangayu, Candipuro District, South Lampung Regency, for the 2022/2023 academic year. 2) Knowing the magnitude of the influence of teacher motivation on teacher performance at MTs Nurul Hikmah Cintamanis Baru, Banyuasin. 3) Knowing the magnitude of the influence of Work Culture and Teacher Motivation together on teacher performance at MTs Nurul Hikmah Cintamanis Baru, BanyuasinAcademic Year. To overcome this problem the researcher conducted research using the survey method by using a questionnaire as an instrument for collecting research data and interview methods to find out how culture and work motivation affect teacher performance at MTs Nurul Hikmah Cintamanis Baru, Banyuasin. The results of this study found that: 1) in the r product moment table at a significance level of 1% and 5%. For N = 37 at a significant level of 5% = 0.325 so that r count is greater than r table means there is a significant effect and a significant level of 1% = 0.418 is smaller than r count so there is a significant effect. Based on the interpretation table for the r value above, the calculated effect number of 0.994 is included in the 0.90 – 1.00 group which indicates a very strong or very high level of influence. 2) Meanwhile, to express the size of the contribution of the variables X1 and X2 with the Y variable or the determinant coefficient = R2 x 100% = (0.994)2 x 100% = 0.988% and the remaining 99.012% is determined by other variables. 3) Furthermore, to find out the significance of the double effect (R) the following F test is calculated: Fcount = R2/k/(1-R2)/(n-k-1) = 313.27 for Ftable = F(1-0.05)[( db = k), (db = n-k-1)] so Ftable = F(0.95)(2)(34) = 3.28. Because Fcount ˃ Ftable or 313,27,75 > 3,28, there is a significant influence between work culture and motivation on teacher performance.